Implementasi UU Perlindungan Anak UU No 35 Tahun 2014 Terhadap Perkawinan di Bawah Umur dalam Masyarakat Budaya Melayu - Mhd Tondi Irawan; Adwiyah nasution; Herlina Hanum (Jurnal Smart Hukum (JSH), 2023)
This research is entitled Implementation of Child Protection Law No. 35 of 2014 Against Underage Marriage in Malay Cultural Society. This research takes the formulation of the problem: Has Law No. 35 of 2014 been implemented on the Marriage of Minors in Malay Indigenous Peoples? What are the obstacles to the implementation of Law No. 35 of 2014 on the Marriage of Minors in Malay Indigenous Peoples? What is the effect of underage marriage according to Malay custom? This type of research is a combination of normative (doctrinal) research and empirical research. This research was conducted in Tanah Merah District, South Binjai, Grand Marcapada Indah Complex Block F3 Kotamadaya Bijai. The approach method in this paper is using the normative juridical method because the target of this research is laws and rules. Based on the research found cases of child marriage according to Law No. 35 of 2014 by using Malay cultural customs. Name: Susilawati Saleh Age: 16 years old (married) Religion: Islam Tribe: Malay Address: Jalan Gunung Sinabung Housing Grand Marcapada Indah Block F3 Tanah Merah District, South Binjai. And 2nd Finding. Name : Khoirunasah Married Age : 15 Years Married Year : 2015 Father's Name : Harun , Mother's Name ; Nani. Marriage Address: Bulu Cina, Hamparan Perak District. From the results of the study, it was concluded that Law N0 35 of 2014 had been implemented against the marriage of minors in the Malay indigenous community. External Factors.